KEGAGALAN DINI PERKERASAN JALAN AKIBAT PELAKSANAAN KONSTRUKSI - Yunus, Ruslan M. (MEKTEK, 2006)
Liability for construction failure is main issue in construction industry. Production process that involves many parties with various interests caused liability allocation for the construction failure to be complicated. One of cause premature failure is inappropriate between product and contract stipulation. This article aim to study in construction premature failure the study process through regulation analysis and previous research result related to cause premature failure during construction phase. The study found some problems which still require to be assured, and vital importance to be developed in UU No. 18 / 1999 about Construction Service as failure definition, period of liability, assessment criterion to failure still require to be developed to reduce assessor subjectivity, and level of compensation to the arising out costs and loss in failure case require to estimate.